Complete manifestations of BehÃ§etâs disease - Umami, V; Setiyohadi, Bambang (Indonesian Rheumatology Association, 2010)
BehÃ§etâs disease (BD) is a chronic, relapsing, inflammatory disease characterized by recurrent oral aphthae and any of several systemic manifestations that include genital aphthae, ocular disease, skin lesions, neurologic disease, vascular disease, or arthritis. Hippocrates may had described BD in the fifth century B.C.; however, the first official description of the syndrome was attributed to the Turkish dermatologist Hulusi BehÃ§et in 1924. In 1930, the Greek physician Adamantiades reported a patient with inflammatory arthritis, oral and genital ulcers, phlebitis, and iritis.1 Since then, the syndrome has been referred to as BD.1,2 The manifestations of BD are thought to be caused by an underlying vasculitis. Although this disease is recognized worldwide, the prevalence is highest in the eastern Mediterranean, the Middle Eastern, and East Asian countries, thus the nickname Silk Road disease. The disease tends to be more severe in areas where it is more common. Prevalence rates all over the world are increasing, probably because of improved recognition and reporting. BehÃ§etâs disease occurs primarily in young adults. The mean age at onset is between 25 and 30 years. The incidence of disease in males and females is approximately equal along the Silk Road, but in Japan, Korea, and Western countries the disease occurs more frequently in women. Caseconfirmation can be challenging because many patients labeled as having BD have oral ulcers as the primary or sole manifestation.3